Pengaruh Implementasi Kebijakan Program Keluarga Harapan Terhadap Kesejahteraan Masyarakat di Kecamatan Cimahi Selatan Kota Cimahi - Rahmatillah, Saeful Anwar; Rochaeni, Atik; Fujilestari, Noer Apptika; Yamardi (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research is entitled “The Effect of the Implementation of the Program Keluarga Harapan Policy on Community Welfare in South Cimahi District, Cimahi City”. The research objective is to analyze the impact of the implementation of the Program Keluarga Harapan (PKH) policy on community welfare in Cimahi Selatan District. The method used is a combination (mixed methods) with a sequential explanatory model, involving 154 respondents as samples and informants such as the Head of Linjamsos and PFM, Kasi Linjamsos and PFM, PKH Social Coordinator of Cimahi City, and KPM of South Cimahi District. Data collection techniques include literature study, questionnaires, interviews, and observations, with analysis using product moment correlation techniques. The results showed that the implementation of PKH policy in Cimahi Selatan Sub-district was in the good category, with an average score of 2.64 (88.00%). The dimensions of communication and bureaucratic structure get the highest score (2.67 or 89%), while the resource aspect has the lowest score (2.60 or 86%). For community welfare, the mean score was 2.61 (87.00%), with the prosperous life aspect getting the highest score (2.67 or 89%) and good adjustment getting the lowest score (2.56 or 85%). Hypothesis testing showed a p-value of 0.04 (<0.05), indicating that the research hypothesis is accepted. The magnitude of the effect of PKH policy implementation on community welfare is 0.85 (85%).